American denominational history: perspectives on the past, prospects for the future - Harper, Keith (Religion and American culture, 2008)
Catholic distinctiveness and the challenge of American denominationalism -- New directions on the congregational way -- Presbyterians in America : denominational history and the quest for identity -- From the margin to the middle to somewhere in between : an overview of American Baptist historiography -- "Everything arose just as the occasion offered" : defining Methodist identity through the history of Methodist polity -- Black Protestantism : a historiographical appraisal -- Mormon historiography -- Interpreting American Pentecostal origins : retrospect and prospect -- "We're all evangelicals now" : the existential and backward historiography of twentieth-century evangelicalism